A Comparative Study to Assess the Quality of Different Marketed Brands of Metformin HCl - Alnedhary, Anass A.; Numan, Abdualqawi A.; AL-Hammadi, Mahfoudh M.; Murshed, Fatima A.; Dubais, Huda M. (PSM Biological Research, 2021)
The present work reported quality assessments and stability studies of metformin hydrochloride in various brands with a label claim of 500 mg marketed in the capital Sana'a, Yemen. Physical parameters including thickness, diameter, hardness, friability, weight variation, and disintegration time were evaluated. Assay tests and dissolution rates were carried out using HPLC-UV and spectrophotometric methods respectively. All investigations were done at purchase time and after one month, three months, and six months storage conditions under an accelerated stability environment (40±2°C and 75±5% RH). The results showed that all brands of metformin hydrochloride complied with the official specification for thickness, diameter, hardness, friability, weight variation, disintegration time, dissolution, and assay tests. Assay evaluation results revealed that all tested brands have met the acceptance criteria (95%-105%) with exception of ME1 samples stored for three months whose values (94.29%) were lower than the acceptable limit and ME4 (105.95%) and ME5 (105.66%) stored for one month that was higher than the acceptable range.